Behavioral Biases in Marketing - Daniel Guhl; Daniel Klapper; Katharina Massner; Martin Spann; Lucas Stich; Narine Yegoryan (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Psychology and economics (the mixture of which is known as behavioral economics) are two fundamental disciplines underlying marketing. Various marketing studies document the non-rational behavior of consumers, even though behavioral biases might not always be consistently termed or formally described. In this review, we identify empirical research that studies behavioral biases in marketing. We summarize the key findings according to three classes of deviations (i.e., non-standard preferences, non-standard beliefs, and non-standard decision-making) and the marketing mix instruments (i.e., product, price, place, and promotion). We thereby introduce marketing researchers to the theoretical foundation of and terminology used in behavioral economics. For scholars from behavioral economics, we provide ready access to the rich empirical, applied marketing literature. We conclude with important managerial implications resulting from the behavioral biases of consumers, and we present avenues for future research.
Keywords: 330; marketing; behavioral economics; behavioral biases; review